Bullying Education in Adolescents Based on Reflections on James 4:11 - Marthen Mau; Fedirman Dakhi; Suarman Zai; Suardin Zai (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
The phenomenon of bullying in teenagers is a problem that disrupts growth both cognitively, mentally and psychologically. This must be taken seriously considering the impact and risks for teenagers which are very detrimental to both teenagers as victims and as perpetrators and their influence on the civilization of social life. So we need action that can prevent this bullying. Therefore, this research study provides bullying education for teenagers based on the reflection of James 4:11. The method for writing this study uses a descriptive qualitative approach with a literature review method, and collects data through books, journal articles and internet websites as a basis for writing and drawing conclusions. The results of this study are that parents, teachers and other community members can take steps through collaboration that can create a safe and supportive environment for all young people, especially teenagers who need assistance in undergoing their development phase. Appropriate actions in supporting teenagers so that they can recognize God, in imitating God's attitude and character, and His direction, and grow in the good and right way in God's hands so that inappropriate and good behavior, attitudes and character are carried out Adolescence can be reduced by forming an awareness of viewing others as social creatures whose existence is respected and valued.